Teaching wavelets in XploRe - Sigbert Klinke; Yuri Golubev; Wolfgang Härdle; Michael H. Neumann (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
Teachware is a set of computer software tools for computeraided interactive teaching of certain knowledge elements. The construction of teachware for statistical knowledge is a rather young field since it heavily depends on data structures and graphical interaction possibilities. In this paper we present a teachware module for XploRe - a statistical computing environment. We focus on the situation of teaching wavelets, a technique for adaptation of spatial inhomogeneity.
urn:nbn:de:kobv:11-10060862
Keywords: 330